Reading the everyday - Moran, Joe, 1970-; Arts and Humanities Research Board (Great Britain) (Milton Park, Abingdon, Oxon ; New York : Routledge, 2005)
"Drawing on the work of continental theorists such as Henri Lefebvre, Michel de Certeau, Marc Auge and Siegfried Kracauer, Joe Moran explores the concrete sites and routines of everyday life and their representation in political debate, news media, material culture, sitcoms, reality TV shows, photography, CCTV and webcams." "Moran aims to rethink notions of everyday life within cultural studies, which have traditionally focused on questions of popular culture, consumption and lifestyle. He investigates some of the most under-explored, banal aspects of quotidian culture, such as office life, commuting, car parking, motorways, new towns and mass housing." "Reading the Everyday shows that analysing supposedly 'boring' phenomena can help us to make sense of cultural and social change; and it argues that the everyday has become a space for a new kind of 'post-political' politics which has obscured profound changes in work, domestic and public space."--BOOK JACKET.
Bibliography : p. 177-196.
Keywords: Sociology, Urban; Civilization, Modern; Popular culture; Quotidian; -- Everyday life